Screwball comedy and film noir unexpected connections - Renzi, Thomas C. 1948- (McFarland, 2012)
"This illustrated overview presents a comprehensive comparative analysis of Screwball Comedy and Film Noir, two popular Hollywood genres that emerged at nearly the same time. Two appendices offer a comprehensive filmography of Screwball comedies from 1934 through 1954 and a selected filmography of Film Noir titles, covering 1941 through 1958"--Provided by publisher